Socio-cultural factors associated with morbidity and mortality: A study from Eastern Nepal - Jha, Nilambar; Bhattarai, S; Niraula, SN (Health Renaissance, 2017)
Background: Today there has been a change in the perception of disease from germ theory to the involvement of multiple factors in the causation. Methods: With this notion, this cross sectional study made an effort to delineate the socio-cultural factors associated with health in six teaching districts of B.P. Koirala Institute of Health Sciences in the Eastern region of Nepal among the mothers of reproductive age surveying 1985 households. Results: This study revealed association of chronic disease and acute illness with various socio-demographic variables like religion, ethnicity, family size, number of children, respondent’s literacy and occupation. Number of jobholders in the family and poverty line were found to be associated with acute illness. Treatment of shaman healers and restrictions during pregnancy period showed association with health inequalities. Mortality in the family was associated with ethnicity, number of children, and literacy of respondent. Conclusion: As a consequence of these associated factors, the effective utilization of the modern health facilities may not be proper which may lead to ill health consequences. Multifaceted development program from the government along with effective awareness program can help out the people to combat the evil of health life. Health Renaissance 2015;13 (3): 114-128